2012
DOI: 10.3109/09286586.2012.670742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with Dry Eye Syndrome among Senior High School Students in a County of Shandong Province, China

Abstract: Senior high school students are a neglected population with a high prevalence of DES. Preventive measures directed against risks factors for DES among senior high school students may help reduce the prevalence and provide a positive impact on students' health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
70
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 19 publications
9
70
4
5
Order By: Relevance
“…28 However, the lower prevalence compared to the current study might be due to the hospital-based nature of the former study, which is likely to underestimate the true dry eye prevalence, because most dry eye patients resort to selfmedication. 29 Yun et al 25 reported a prevalence of 50.6% via OSDI among university students in Korea which is similar to 48.1% via OSDI in this study, whereas Zhang et al 29 reported a prevalence of 23.7% among senior high students in China. The prevalence rate here showed a relatively high prevalence of dry eye among undergraduate university students in Ghana.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…28 However, the lower prevalence compared to the current study might be due to the hospital-based nature of the former study, which is likely to underestimate the true dry eye prevalence, because most dry eye patients resort to selfmedication. 29 Yun et al 25 reported a prevalence of 50.6% via OSDI among university students in Korea which is similar to 48.1% via OSDI in this study, whereas Zhang et al 29 reported a prevalence of 23.7% among senior high students in China. The prevalence rate here showed a relatively high prevalence of dry eye among undergraduate university students in Ghana.…”
Section: Discussionsupporting
confidence: 81%
“…The total OSDI score was calculated for each participant based on the following formula: sum of scores of all questions answered multiplied by 25 divided by the total number of questions answered. Participants were grouped into 4 categories by the OSDI score: normal (scores 0-12), mild dry eye symptoms (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate dry eye symptoms (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and severe dry eye symptoms (33-100). 26 The standard patient evaluation of eye dryness (SPEED) questionnaire developed by Tear-Science (Morrisville, NC) is a valid and repeatable questionnaire for dry eye.…”
Section: Questionnairesmentioning
confidence: 99%
“…Recent epidemiological studies report dry eye symptoms in about 25% of high school students and 30 – 65% office workers. [15-21]…”
Section: Introductionmentioning
confidence: 99%
“…For China, the largest developing country, new lifestyles driven by information technology and the rapid ageing process have brought DED a severe public health concern in both young and old generations [4,22,23]. The latest systematic review and meta-analysis of DED prevalence in China conducted by N Liu, et al revealed a pooled DED prevalence of 17.0%, by using prevalence estimates from 12 individual studies.…”
mentioning
confidence: 99%